The Lottery: A Study of Narrative Irony and Its Role in Exploring Human Nature - Devita Luci Avista; Garnis Niken Ayu Salindri (STIKes Ibnu Sina Ajibarang, 2024)
The purpose of this study was to identify and analyze various forms of narrative irony contained in Shirley Jackson's short story